Influence of static, dynamic, and combined static-dynamic stretching on sprint time, reaction time, peak force and peak power production in young male sprinters - Washif, Jad Adrian (2014)
The purpose of this study was to examine the influence of static, dynamic, and combined static-dynamic stretching on sprint time, reaction time, peak force and peak power production in sprinters. Thirteen (n = 13) young male sprinters performed three different stretching methods including static stretching (SS), dynamic stretching (DS) and combined static-dynamic stretching (CSDS). Electronic timing-gates with reaction measurement pads were used to measure sprint time (50 m) and reaction time, and a force-plate was utilised to assess peak force (PF) and peak power (PP) production. The results indicated statistically significant differences among the three stretching methods for sprint time (p = .001) and reaction time (p = .015) but not for peak force (p = .483) and peak power (p = .458) even though DS elicited better performance. DS evoked the best sprint time (6.18 s + .11), followed by CSDS (6.33 s + .10) and then SS (6.37 s + .11). These results were similar for reaction time with the best results coming after performing DS (0.221 s + .039), but followed by SS (0.257 s + .047), and then CSDS (0.293 s + .075). These results suggested that DS induced better sprint time and reaction time, SS resulted in the slowest sprint, and the lowest PF and PP production, while CSDS resulted in the slowest reaction time. The reasons for better performance following DS may be associated with greater neuromuscular activation compared with other methods. However, the benefit from DS may have been diluted when combined with SS. SS and CSDS prior to high-speed, high-power and short-term activities are not recommended as they seem to have a deleterious influence on performance. Therefore, the application of DS for sprint time and reaction time seem to be able to increase the ability of muscle to perform maximally.